A novel SLC37A4 missense mutation in GSD‐Ib without hepatomegaly causes enhanced leukocytes endoplasmic reticulum stress and apoptosis. Issue 1 (5th December 2020) - Xu, Qianyun; Tang, Haiyan; Duan, Liping; Zuo, Xiaoxia; Shi, Xiaoliu; Li, Yisha; Zhao, Hongjun; Zhang, Huali
Abstract: Background: Glycogen storage disease (GSD) type Ib is an autosomal recessive disease caused by defects of glucose‐6‐phosphate transporter (G6PT), encoded by the SLC37A4 gene. To date, over 100 mutations have been revealed in the SLC37A4 gene. GSD‐Ib patients manifest a metabolic phenotype of impaired blood glucose homeostasis and also carry the additional complications of neutropenia and myeloid dysfunction. Methods: Here, we present two daughters with an initial diagnosis of gout in a Chinese consanguineous family. Whole‐exome sequencing was performed to identify the mutations. The mechanism of leukocytopenia was investigated. Results: Whole‐exome sequencing analysis of the proband identified a novel homozygous p.P119L mutation in SLC37A4, leading to a diagnosis of GSD‐Ib. We found that the potential pathogenic p.P119L mutation leads to an unusual phenotype characterized by gout at onset, and GSD‐Ib arising from this variant also manifests multiple metabolic abnormalities, leukocytopenia, and anemia, but no hepatomegaly. The leukocytes from the proband showed increased mRNA levels of sXBP‐1, BIP, and CHOP genes in the unfolded protein response pathway, and enhanced Bax mRNA and caspase‐3 activity, which might contribute to leukocytopenia. Conclusion: Our findings broaden the variation spectrum of SLC37A4 and suggest no strict genotype–phenotype correlations in GSD‐Ib patients. Abstract : Here, we report two daughters with the initial diagnosis of gout in a Chinese consanguineous family. We found that the potential pathogenic P119L mutation leads to an unusual phenotype characterized by typical gout at onset, and GSD‐Ib arising from this variant also manifests multiple metabolic abnormalities, leukocytopenia, and anemia, but no hepatomegaly. The leukocytes from the proband showed increased mRNA levels of sXBP‐1, BIP, and CHOP genes in the unfolded protein response pathway, and enhanced Bax mRNA and caspase‐3 activity, which might contribute to leukocytopenia.